Chronic Subdural Hematoma and Massive Subgaleal Hematoma Following Pediatric Minor Head Trauma - Alloyna, Dhika; Tala, Ihsan Z (Talenta Universitas Sumatera Utara, 2019)
Subdural hematomas result from injury to the bridging cortical veins or from extension of intracerebral contusion in the subarachnoid space. Chronic subdural hematomas are usually observed in infants and result from an undiagnosed or conservatively treated acute subdural hematoma. Treatment depend on the extension and localization of the hematoma. Subgaleal hematoma is caused by rupture of emissary veins and located between the periosteum and the scalp galea aponeurotica extending from the orbital ridges to the nuchal ridge. A 6-year-old boy presented with a fluctuant mass over the scalp following a minor head injury 4 days earlier with history of headache and vomiting. He had undergone craniotomy procedure ten months earlier due to brain abscess drainage, post operative head CT revealed no abnormal radiologic findings and no clotting disorder was found before. A plain CT head revealed a thick isodense subdural collection overlying the left cerebral convexity and presentation of massive circumferensial subgaleal hematoma. Laboratory findings suggest progressive bleeding with low hemoglobin level of 6.8 g/dL but normal coagulation panel. The patient was managed surgically with a left-sided craniotomy hematoma evacuation. The previous subgaleal and subdural drains inserted gradually showed less production 3 days after surgery were withdrawn subsequently. As the clinical symptoms resolved, he was discharged with a slight intermitten headache. The patient was loss to follow-up so there were no post operative imaging. The majority of chronic subdural hematoma which are frequently encountered in neurosurgical practice, ideally treated with surgical drainage. Minor head trauma can lead to chronic subdural hematoma and massive subgaleal hematoma and these patients should be evaluated for underlying coagulopathy.